2015
DOI: 10.1002/gcc.22256
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of MED12 mutations in fibroadenomas and phyllodes tumors of the breast—implications for tumor biology and pathological diagnosis

Abstract: Somatic mutations in exon 2 of MED12 have been described in benign and malignant smooth muscle cell tumors suggesting a functional role in these neoplasms. Recently fibroadenomas of the breast were also reported to harbor MED12 mutations. Hence, we explored MED12 mutations in fibroepithelial tumors of the breast, histological subtypes of fibroadenomas and phyllodes tumors, to validate and extend previous efforts. Using conventional Sanger sequencing, we profiled 39 cases of fibroepithelial breast tumors compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
44
3
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 34 publications
12
44
3
2
Order By: Relevance
“…We found that the frequency of MED12 mutant tumors is higher in benign than in intermediate/malignant PT although the difference is not statistically significant. Similar results have been reported elsewhere [14][15][16][17][18] and all these reports Table 1), suggesting that MED12 mutation is not implicated in the pathogenesis of about two-thirds of malignant PTs. However, the genetic change(s) responsible for the pathogenesis of malignant PTs remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the frequency of MED12 mutant tumors is higher in benign than in intermediate/malignant PT although the difference is not statistically significant. Similar results have been reported elsewhere [14][15][16][17][18] and all these reports Table 1), suggesting that MED12 mutation is not implicated in the pathogenesis of about two-thirds of malignant PTs. However, the genetic change(s) responsible for the pathogenesis of malignant PTs remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been reported by other investigators [16][17][18]. The pathogenesis of FAs and PTs remains largely unknown but these observations seem to indicate a significant involvement of MED12 mutation in their pathogenesis.…”
Section: Introductionsupporting
confidence: 89%
“…The frequency of MED12 somatic mutations reported ranges from 45% to 80%, not significantly different between fibroadenomas and phyllodes tumours, although some authors report a lower frequency in malignant phyllodes tumours10 11 while other studies show no significant difference among phyllodes tumours of different grades 2 12. In uterine leiomyomas, mutations of MED12 are common, but are rare in its malignant counterpart the leiomyosarcoma 13–15.…”
Section: Discussionmentioning
confidence: 98%
“…The most recent genome sequencing studies have identified frequent MDM12 somatic mutations in fibroadenoma and PT, suggesting these 2 entities may share a common origin. [6][7][8][9][10] This review will address some of the diagnostic problems that are encountered in routine practice and provide molecular/genetic updates on PTs of the breast.…”
mentioning
confidence: 99%